MODAL SOSIAL ANGGOTA KELOMPOK TANI GEMAHRIPAH DALAM MENGATASI HAMA DAN PENYAKIT TANAMAN DI DESA WIROWONGSO KECAMATAN AJUNG KABUPATEN JEMBER - Sofian Ardiansyah; Triwila Nindra Putra Perdana; Ferdiansyah Adi Permana (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The agricultural sector is currently often a serious concern by the government, this is due to the many problems that often attack the agricultural sector. The main problems that often become disruptions to the agricultural sector are the problems of pests and diseases. The goal of this research is to determine the social capital of members of the Gemahripah farmer group for solving plant pest and disease problems in Wirowongso Village, Ajung District, Jember Regency. The method of determining the research location in this research uses purposive method. The research method uses qualitative analysis and case studies. The method of data collection uses the method of interviews, observation and documentation to obtain primary and secondary data. Data analysis used the Miles and Huberman analysis models starting from data collection, data reduction, data presentation and conclusions / verification. The results showed that there were 5 main elements of social capital of members of the Gemahripah farmer group for solving the problems of pests and plant diseases, including participation in networks, respirocity, trust, social norms and values.